Bioabsorbable magnesium screw versus conventional titanium screw fixation for medial malleolar fractures - Hasan May; Yusuf Alper Kati; Gurkan Gumussuyu; Tuluhan Yunus Emre; Melih Unal; Ozkan Kose (Journal of Orthopaedics and Traumatology, 2020)
Abstract Background It is still unknown whether bioabsorbable magnesium (Mg) screws provide an advantage over titanium screws in the treatment of medial malleolar (MM) fractures. The purpose of this retrospective study is to compare the clinical and radiological outcomes of MM fractures fixed with either bioabsorbable Mg screws or conventional titanium screws. Materials and methods A cohort of 48 patients with MM fractures who underwent compression screw fixation was retrospectively reviewed. Twenty-three patients (16 male, 7 female; mean age: 37.9 ± 17.7 years) were treated with bioabsorbable Mg screws, and 25 patients (14 male, 11 female; mean age: 45.0 ± 15.7 years) were treated with conventional titanium screw fixation. All patients were followed up for at least 1 year, with a mean time of 24.6 ± 10.5 months (12–53 months). The American Orthopedic Foot and Ankle Society (AOFAS) scale was used to evaluate the clinical results. The Kellgren–Lawrence (KL) osteoarthritis grading was used to evaluate posttraumatic osteoarthritis on final ankle radiographs. Fracture union, rate of implant removal, and complications were recorded. Comparative analysis of two independent groups was performed using the chi-squared test and the Mann–Whitney U-test. Results The two groups were comparable concerning demographic and clinical characteristics. Age (p = 0.146), sex (p = 0.252), side (p = 0.190), MM fracture type (p = 0.500), associated fractures (p = 0.470), and follow-up period (p = 0.903) were similar between the groups. At final follow-up examination, AOFAS score (p = 0.191) was similar between groups. Fracture union was achieved in all cases. Grade of posttraumatic osteoarthritis, according to KL, was equally distributed in both groups (p = 0.074). No deep infection or osteomyelitis was seen. Five patients in the titanium screw group underwent implant removal, due to pain in three of them and difficulty in wearing shoes in the other two (p = 0.031). Implant removal was performed after a mean of 14.2 ± 3.1 months (12–19 months). Conclusions Bioabsorbable Mg and titanium screws had similar therapeutic efficacy in MM fracture fixation regarding functional and radiological outcomes. However, the rate of implant removal was higher with titanium screws. Bioabsorbable Mg screws may be a favorable fixation option since secondary implant removal procedures can be prevented. Level of evidence Level IV, Retrospective case series.